Unusual chromosome numbers in Paspalum L. (Poaceae: Paniceae) from Brazil - Peñaloza, A. P. S. (2008)
Somatic chromosome numbers were determined for 20 new germplasm accessions of Paspalum, belonging to 17 species collected in Brazil. Chromosome number is reported for the first time for P. reduncum (2n = 18), P. cinerascens (2n = 20), P. cordatum (2n = 20), P. filgueirasii (2n = 24), P. ammodes (2n = 36), P. bicilium (2n = 40), P. heterotrichon (2n = 40), and P. burmanii (2n = 48). New cytotypes were confirmed for two germplasm accessions of P. carinatum (2n = 30) and P. trachycoleon (2n = 36), one of P. clavuliferum (2n = 40) and one of P. lanciflorum (2n = 40), indicating variability in these species. The remaining chromosome numbers reported here confirm previous counts. The unexpected chromosome numbers 2n = 18, 24, 36, and 48 in Paspalum species, which are usually shown to be multiples of 10, suggest that much more collection and cytogenetic characterization are necessary to assess the whole chromosomal and genomic multiplicity present in the genus, which seems to be much more diverse than currently thought to be.